Role-taking in two micro-community sign languages: Phylogenetic insights - Martinod, Emmanuella (Frontiers in Communication, 2022)
This paper aims to examine the use of role-taking constructions in two micro-community SLs: Yucatec Maya SL (YMSL), and Soure SL. Similar proportions of spontaneous conversations and elicited data from both SLs were examined. Various role-taking types were quantified and changes in gaze direction were annotated. Results show (i) a greater diversity of role-taking produced in YMSL, including complex role-taking (i.e. multiple perspectives or role-taking produced alongside lexical units), and (ii) changes in gaze direction before and after the production of role-taking constructions in both SLs. First, this suggests a phylogenetic development between the two SLs partly observable from the study of role-taking through the conceptual lens of bifurcation of the signer’s intent. More broadly, analysis of SLs phylogenesis would benefit from this kind of examination using analytical concepts relevant for SLs. Second, results seem to indicate that SLs phylogenesis would share similarities with SLs ontogenesis. Indeed, the less socially integrated analyzed SL (Soure SL) would display a less advanced degree of bifurcation since little complex role-taking constructions are observed. This is in line with the way these structures are acquired late by SL learners. Further studies on other micro-community SLs would be needed to precise this.